Educational Development through Community Learning Center Management for Street Children - Rista Harimurti, Eka (International Journal of Psychosocial Rehabilitation, 2020)
Education has an important role in the progress in the country. Based on this, educational development in Indonesia becomes a priority for the government and the community. Education is the right for a citizen without exception for street children. Educational development has the purpose of fulfilling the education right and creating the quality of the human in which the industrial world challenges to face the globalization era. The State as an educational stakeholder organizes formal, non-formal and informal education. Community Learning Center (CLC) is a non-formal education and a center for empowerment activities and public awareness to participate in educational development. This article gives describe CLC management for street children through the management functions, the implementation for CLC educational program as follows (1) educational programs planning based on the needs analysis and characteristics of students; (2) educational program implementation is carried out through system approach and organizational structure; (3) educational program supervision is carried out by monitoring and evaluating. This article can be used as a recommendation to related parties such as CLC managers, the government as policymakers, street children as part of learning citizens, researcher as educational practitioner, academics and the public about how educational development is carried out through nonformal education management, namely CLC.